Answers

2014-06-14T11:11:33+08:00
X^{2} -2x=3  then 

 standard form this is ax^{2}+bx+c=o 

x^{2} - 2x - 3 = 0

the ROOT
a=2, b=-2, c=-3



1 1 1
2014-06-14T11:23:28+08:00
Here! Hope this helps:)
1 5 1
Thank you. :)) It gives me an idea but I really can't answer my homework. You and my teacher have a different solution and when I'm trying my solution, it's really not right. :( I need to follw my teacher's solution.
Ok if that's the case, can you post your solution then so that I can see where you went wrong if you dont mind:) I'm really willing to help:)